Building of Effective Control and Management System for Injection Horizontal Wells During Waterflooding; SPE Russian Petroleum Technology Conference - Galeev R. Rail; Rybakov R. Roman; Yakovlev A. A. Andrey Alexandrovich; Kayeshkov I. Ilya; Simakov S. Sergey; Fayzullin I. Ildar; Sagirov A. Aleksandr; Feoktistov R. Roman; Suleymanov A. Ayyar (2018, 2018)
Title screen